Oral Fluoroquinolone or Trimethoprim-Sulfamethoxazole vs ß-Lactams as Step-Down Therapy for Enterobacteriaceae Bacteremia: Systematic Review and Meta-analysis - Punjabi, Chitra (Open Forum Infect Dis, 2019)
BACKGROUND: Using published data, we sought to compare outcomes in patients transitioned to either oral fluoroquinolones (FQs) or trimethoprim-sulfamethoxazole (TMP-SMX) vs ß-lactams (BLs) after an initial intravenous (IV) course for gram-negative rod (GNR) bacteremia. METHODS: We conducted a systematic review of PubMed and EMBASE and published IDWeek abstracts. We included studies that reported all-cause mortality and/or infection recurrence in patients transitioned to oral FQ/TMP-SMX and BLs. RESULTS: Eight retrospective studies met inclusion criteria with data for 2289 patients, of whom 65% were transitioned to oral FQs, 7.7% to TMP-SMX, and 27.2% to BLs. Follow-up periods ranged from 21 to 90 days. All-cause mortality was not significantly different between patients transitioned to either FQ/TMP-SMX or BLs (odds ratio [OR], 1.13; 95% confidence interval [CI], 0.69–1.87). Overall recurrence of infection, either bacteremia or the primary site, occurred more frequently in patients transitioned to oral BLs vs FQs (OR, 2.05; 95% CI, 1.17–3.61). Analysis limited to recurrent bacteremia was similarly suggestive, although limited by small numbers (OR, 2.15; 95% CI, 0.93–4.99). However, based on known pharmacokinetics/pharmacodynamics, prescribed ß-lactam dosing regimens were frequently suboptimal. CONCLUSIONS: In the step-down IV to oral treatment of GNR bacteremia, we found insufficient data regarding outcomes after oral TMP-SMX; however, selection of an FQ over commonly utilized ß-lactam regimens may reduce chances of infection recurrence. Although this may be a class effect, it may simply be the result of inadequate dosing of ß-lactams. Additional investigations are warranted to determine outcomes with TMP-SMX and optimized oral ß-lactam dosing regimens.